Pemberian kompres hangat efektif untuk pemulihan peristaltik usus pasien post operasi dengan anestesi umum - Asniah Syamsuddin (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: Almost every patient with major surgery or surgery who uses general anesthesia after surgery does not take any action to help with intestinal peristalsis. Giving warm compresses is one way to reduce muscle spasms, increase and increase blood flow.Objectives: The purpose of this study was to study the solution of warm compresses to postoperative intestinal peristalsis recovery with general anesthesia.Methods: The design of this study was a quasi-experimental design with nonequivalent control group design, a sample of 16 respondents who were taken by consecutive sampling technique. The research was conducted at the Meuraxa Hospital Hospital Banda Aceh in 2019. The data was processed using statistical tests using paired sample t-test.Results: The results of the study have shown that there is the effectiveness of giving warm compresses to the recovery of peristalsis in the experimental group with a value of p= 0.000 (p < 0.05), and the independent t-test shows that there is a significant difference in intestinal peristalsis between the experimental group and the control group in post patients. surgery under general anesthesia with a value of p= 0.022 (p < 0.05).Conclusion: The effectiveness of warm compresses on the recovery of intestinal peristalsis in the experimental group and the control group in postoperative patients with general anesthesia. It is hoped that patients and nurses can apply warm compresses after surgery with general anesthesia